The Mediating role of Technology Competences, Supply Chain Technology between Supply Chain Management, Total Quality Management and Firms Supply Chain Performance in Indonesian Textile Sector - Slamet Riyadi (International Journal of Supply Chain Management, 2020)
The prime objective of this study is to investigate the association among the practices of supply chain management (SCM), total quality management (TQM), through the information technology (IT) competencies and the adoption of innovation in SCM with the firm’s supply chain performance (FSCP). Moreover, this study similarly tries to find out the mediating role of the IT competencies and the adoption of SC technology in the association between SCM, TQM and the FSCP. This study is based on a sample of firms related to the textile industry of Indonesia. Smart PLS-3 is used for data analysis that is gathered from Indonesia’s textile firms, in order to attain the objective of the research. The results of the study are consistent with the hypotheses. With respect to the association among TQM, SCM and supply performance, the IT competencies and SC technology mutually act as mediators. The conclusion reached will be beneficial for the policymakers and researchers especially with regard to the implications of IT in the area of strategic and operations management.